2018
DOI: 10.5817/cp2018-1-5
|View full text |Cite
|
Sign up to set email alerts
|

“Everything under control?”: Privacy control salience influences both critical processing and perceived persuasiveness of targeted advertising among adolescents

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…From the individual perspective, such control can also involve providing false information to the data collector (Miltgen & Smith, 2019). Regarding the personalization process, it includes privacy control menus that allow individuals to opt-out from processing for personalization (meaning not seeing personalized ads; see Zarouali et al, 2018). Finally, regarding data sharing, the literature proposes privacy settings that allow individuals to opt-out from third parties accessing their personal information (Tucker, 2014).…”
Section: ) Examples Of Personalization Processes Include Amentioning
confidence: 99%
See 3 more Smart Citations
“…From the individual perspective, such control can also involve providing false information to the data collector (Miltgen & Smith, 2019). Regarding the personalization process, it includes privacy control menus that allow individuals to opt-out from processing for personalization (meaning not seeing personalized ads; see Zarouali et al, 2018). Finally, regarding data sharing, the literature proposes privacy settings that allow individuals to opt-out from third parties accessing their personal information (Tucker, 2014).…”
Section: ) Examples Of Personalization Processes Include Amentioning
confidence: 99%
“…While high transparency may contribute to higher awareness among individuals, it does not automatically imply higher control. In cases of high transparency and low actual control, the same transparency mechanisms are in place as described above, but they either do not come with the possibility for action by the user (or have very limited options) to stop data collection (Zarouali et al, 2018), or they do not have opt-out signs in the app or web interface that would allow the user to impact the processing for personalization (Joo, 2018).…”
Section: Example 2: High Transparency Low Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…profile targeting; van Reijmersdal et al, 2017). Since the emergence of personalized advertising, a few studies have specifically examined how teenagers respond to such advertising techniques (Walrave et al, 2016;Zarouali et al, 2017Zarouali et al, , 2018b. These studies found that teenagers respond positively to personalized advertising messages, which can have an effect on their attitudes, brand engagement or purchase intentions.…”
Section: Personalized Advertising and Online Data Collection Targeting Teenagersmentioning
confidence: 99%